TOMOGRAPHIC EXAMINATION OF CHANGES IN MUCOPERIOST OF THE MAXILLARY SINUS AFTER SINUS LIFTING - Shpachynskyi, Oleksandr; Skibitskyi, Vadym; Filippenkova, Larisa; Vasilevskyi, Kostiyntin; Didkovskyi, Vyacheslav; Kopchak, Andrii (The Ukrainian Scientific Medical Youth Journal, 2019)
Restoration of the masticatory function in patients with edentulous posterior maxilla is often challenging due to the severe atrophy of the alveolar ridges and insufficient bone quantity for implant supported dentures. The purpose of this study was to analyze the change in mucoperiost after lateral sinus floor augmentation (LSFA) using cone beam com- puted tomography (CBCT).LSFA procedures using different bovine bone materials with and withaut immediate implan- tation were performed at the Stomatological Medical Center of Bohomolets National Medical University in 87 patients, from 2016 to 2018. CBCT examination was performed before LSFA procedure in all patients, postoperative period: up to 1 month after surgery; and after 6 months, before implant placement or loading. Images were acquired using Planmeca ProMax 3D. Postop- erative CBCT performed in early postsurgical period demonstrated that the number of case with type A decreased significantly from 86,67 to 26,75%. The number of cases with type B radiological picture increased from 20,33% to 26,75 %. Mucoperiost type C was observed in 7,5 vs 41,73%. Type D and E were observed in 13.91 and 2.14% However, the clinical signs of the acute sinusitis or specific complaints were recorded only in 2 cases. In 3 cases radiological findings resembled to F type. According to the results of the present study the minor radiologic changes in mucoperiost morphology were observed preoperatively in 17.12% of patients who underwent LSFA proce- dures. The incidence of sinusitis or graft failure in long term follow up consisted 19.26 % while the frequency of asymptomatic radiological changes was significantly higher. It consisted 68.48 in early and 47.1 % in late (6 months) postoperative period. As the differential diagnosis for such changes based only on clinical and radiological data is difficult, the obtained results prove the im- portance of preoperative endoscopic examination, intraoperative and postoperative control in pa- tients with LSFA and the benefits of multidisciplinary approach of oral and ENT surgeons in asset of indications, ricks of the procedure, postoperative rehabilitation and complication management.